Unraveling the impact of social assistance and capital expenditure on poverty rates in Papua's Region - Nurfatma Restu Mahanani; Geger Adelia (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
The Indonesian government has made various efforts to reduce poverty, including through policies in government spending. The spending realized by the government is expected to be able to encourage an increase in people's welfare and reduce poverty. This study aims to analyze the effect of government spending, especially social assistance expenditure and five types of capital expenditure, on the poverty rate, using data at the regional/city level in the Papua province from 2011 to 2019. This study also uses other supporting variables, namely the Gini ratio, Gross per capita Regional Domestic Product (GRDP), school participation rate, and ratio of community health centers. The data used is secondary data obtained from Statistics, The Audit Board of The Republic of Indonesia (Badan Pemeriksa Keuangan, BPK), and the Ministry of Health. The data analysis technique used in this study is panel data regression analysis with a fixed effect model. The analysis showed that out of the six types of government expenditure studied, only capital expenditure for roads, networks, and irrigation significantly reduces the poverty rate.